A template apnupling vinrtual reality a CAD in an immersive car interior design scenario. (1st January 2013) - Meyrueis, Vincent; Paljic, Alexis; Leroy, Laure; Fuchs, Philippe
In this paper, we introduce a method for using jointly the resources of the virtual reality and CAD. The aim is to improve the designers' productivity, particularly in the automotive field. This paper presents a first approach using a bidirectional link between CAD and virtual reality systems that allows parts product modification during a functional virtual simulation review of a car interior. For this, we propose to use a template that gathers different information necessary for the set-up of the immersive simulation and that allows data exchange for product modification. Our approach has been evaluated through an experimental case based on the modification of a button on a vehicle dashboard. In this context, different interaction paradigms and designer assistances supported by the template have also been addressed.